P-CUBE, A Decoupled Parallel Robot Only with Prismatic Pairs - Li, Weimin; Zhang, Jianjun; Gao, Feng (2006 2nd IEEE/ASME International Conference on Mechatronics and Embedded Systems and Applications, 2006)
A new 3-DOF translational parallel robot, named P-CUBE, is presented in this paper. This robot has decoupled motion in x, y and z axes, and employs only prismatic pairs. The structure and kinematics of the robot are studied, which shows there exist rotational redundant constraints to the moving platform. Some modified structures to avoid the overconstrained situation are also introduced. This machine is suitable for heavy load and has high rigidity, which shows its potential in industry applications